##### Given that B(x) means “x is a bat”, F(x) means “x is a fly”, and

Given that

B(x) means “x is a bat”,

F(x) means “x is a fly”, and

E(x, y) means “x eats y”,

what is the best English translation of ∀x(F(x) → ∀y(E(y, x) → B(y)))?

(A) all flies eat bats

(B) only bats eat flies

(C) every fly is eaten by some bat

(D) every bat eats flies

Answer: B

In the given statement : ∀x(F(x) → ∀y(E(y, x) → B(y)))

∀y(E(y, x) → B(y)) means every bat eats some x

∀x(F(x) → ∀y(E(y, x) → B(y))) means every fly implies it is eaten by every bat

in general all flies are eaten by bat only.